Implementasi Pendidikan Karakter Melalui Kompetensi Pengetahuan PAI dan Kegiatan Religius di SMP IT Andalusia Batam - Lina Karnila; Imam Muslimin; Mulyono Mulyono (Syntax Corporation, 2023)
This study aims to describe and analyze the Implementation of Character Education Through PAI (Islamic Religious Education) Knowledge Competence and Religious Activities in SMP IT Andalusia Batam. This research method uses a qualitative research paradigm using an analytic descriptive approach. The data collection techniques in this study are through observation, interviews and documentation. In addition, the data that has been obtained is then analyzed through the data analysis version of Miles and Huberman, namely data reduction, data presentation, and drawing conclusions or verification. The validity of the data in this study was determined using credibility criteria. To obtain relevant data, the researcher checked the validity of the research data by extending observations, observer persistence, and data triangulation. The results of this study are a) the application of character education through PAI knowledge competency at SMP IT Andalusia Batam is carried out by accustoming students to activities such as getting used to greetings, greetings and mutual respect, getting students used to getting up early, helping others (parents, relatives, neighbours, etc.), congregational dhuha prayers, morning dhikr (rotibbul haddad) and evening dhikr (ma'tsurat), tahsin and tahfidz al-Qur'an activities, brotherhood and devotion; b) the implementation of religious activities at SMP IT Andalusia Batam consists of daily activities and periodic activities. Daily activities include, midday prayers and Asr prayers in congregation, monitoring assisted by each parent/guardian in the morning, evening and evening prayers' activities through the muthaba'ah book or the Andalusian character book, qiyamul layl, muroja'ah memorizing the Qur'an 'an, recitation. While periodic activities include sunnah fasting, infaq/alms, mabit, PHBI and istighotsah.